2014
DOI: 10.1007/s11069-014-1443-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of seismic velocity tomography in rock burst hazard assessment

Abstract: In order to quantitatively evaluate the relationship between the tomographic images of P wave velocity and rock burst hazard, the seismic velocity tomography was used to generate the P wave velocity tomograms during the retreat of a longwall panel in a coal mine. Subsequently, a novel index (bursting strain energy) was proposed to characterize the mining seismic hazard map. Finally, the structural similarity (SSIM) index in the discipline of image quality assessment was introduced to quantitatively assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…However, complex geological setting and mining activities make it extremely difficult to obtain the in situ stress field in time and space. To eradicate this problem, many researchers have studied the P-wave tomography for evaluating the high stress in coal mines [34][35][36].…”
Section: Stress Distribution: a Seismic Computed Tomographymentioning
confidence: 99%
“…However, complex geological setting and mining activities make it extremely difficult to obtain the in situ stress field in time and space. To eradicate this problem, many researchers have studied the P-wave tomography for evaluating the high stress in coal mines [34][35][36].…”
Section: Stress Distribution: a Seismic Computed Tomographymentioning
confidence: 99%
“…e mechanism of rockburst could be a base to effectively monitor and prevent the mine rockburst. From an initial record of the mine rockburst phenomenon to the present in the world, there was a history of 274 years [7][8][9][10][11], and during the period, "strength theory," "rigidity theory," "energy theory," "burst potential theory," "instability theory," and other theories were formed [12][13][14][15][16][17]. ose theories all revealed that the condition and principle of the mine rockburst occurred from different flanks and would play a due promotion role in the study on the mine rockburst.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have been used extensively and successfully in the Earth Sciences to map characteristics of the Earth at great depths, for example, the identification of the Mohorovicic Discontinuity (Moho); see Rawlinson et al (2010) for a description of the history of tomographic techniques. To a lesser extent, these techniques have been applied in the mining environment, which is at a much smaller scale, where correlations between velocities and i) geomechanical characteristics of the rock mass (Cai et al 2014;Hemmati Nourani et al 2017;Watanabe and Sassa 1996), and ii) stress anomalies (Cao et al 2015;Friedel et al 1995Friedel et al , 1997He et al 2011;Hosseini et al 2013;Krauß et al 2014;Luxbacher et al 2008;Ma et al 2016;Young and Maxwell 1992) are evaluated. Much of this work was conducted in soft rock environments (coal mines).…”
Section: Introductionmentioning
confidence: 99%